(3ZQjH GdMOjKs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aVdfG HGdfWb cJGH GdCda HGH GdCda eY GdjGA s
(3BNQgG (B:s
(3hgeG GdSjd hGdMQjb , dCfg dG jgJOi dgeG ceG dG jgJOi ai GdJgeGA hgj GdadGI BNQ GdcJGH s
(3HChdgG ELGRI ef GdeDda dYdi Hf GdeaVd Hf Ydi GdebOSi cJHJ HNW bdjd GdfbWs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs